2013
DOI: 10.14411/eje.2013.004
|View full text |Cite
|
Sign up to set email alerts
|

Developmental temperature, body size and male mating success in fruit flies, Drosophila melanogaster (Diptera: Drosophilidae)

Abstract: Abstract. Body size is one of the most investigated traits in studies of sexual selection in fruit flies of the genus Drosophila. In D. melanogaster, size has often been correlated with male mating success, i.e. larger males were more successful in achieving copulations both in laboratory and field conditions. In the present paper, we investigated if male body size is a sexually selected trait in competitive conditions, when full-sibs that developed at two different temperatures (18 and 25°C) competed for fema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 74 publications
1
9
1
Order By: Relevance
“…Consistently, at 22%, the mating success was 33% below random when focal males were smaller than their competitors. This mating advantage of large males is consistent with laboratory and field observations of most Drosophilid species studied so far (reviewed in Pavkovic‐Lucic and Kekic 2013) and investigations of a diversity of other taxa (Andersson 1994; Andersson and Iwasa 1996). In D. melanogaster specifically, this advantage can manifest itself by larger males physically dominating smaller ones in aggressive interactions (Dow and Schilcher 1975; Partridge and Farquhar 1983; Baxter et al.…”
Section: Discussionsupporting
confidence: 88%
“…Consistently, at 22%, the mating success was 33% below random when focal males were smaller than their competitors. This mating advantage of large males is consistent with laboratory and field observations of most Drosophilid species studied so far (reviewed in Pavkovic‐Lucic and Kekic 2013) and investigations of a diversity of other taxa (Andersson 1994; Andersson and Iwasa 1996). In D. melanogaster specifically, this advantage can manifest itself by larger males physically dominating smaller ones in aggressive interactions (Dow and Schilcher 1975; Partridge and Farquhar 1983; Baxter et al.…”
Section: Discussionsupporting
confidence: 88%
“…Males were least likely to engage in copulation at the highest ambient temperature and the highest developmental temperature. Similar effects of temperature on mating likelihood have been reported in the hemlock looper Lambdina fiscellaria (Delisle et al, 2016) and the polyphenic butterfly B. anynana (Westerman & Monterio, 2016), whilst in Drosophila pseudoobscura and Drosophila melanogaster rearing temperature had no effect on the likelihood of female re-mating (Taylor et al, 2017;Pavković-Lučić & Kekić, 2013 sudeva et al (2014) reported that male C. maculatus reared at 33°C had the smallest relative and absolute testes size in comparison to males reared at cooler temperatures. Thus, thermal stress associated with high developmental temperature appears to impact negatively on both reproductive physiology and behaviour in this species.…”
Section: Discussionmentioning
confidence: 57%
“…Because of its myriad ecological consequences-from individuals (e.g., (Glasheen & McMahon 1996;Hurlbert, Ballantyne IV & Powell 2008;Pavković-Lučić & Kekić 2013)) to ecosystems (e.g., (Brown et al 2004;Riede et al 2011;Trebilco et al 2013))-body size is one of the most important functional traits. Body size controls energetic demands (Gillooly et al 2001;Brown et al 2004), diet breadth (Wasserman & Mitter 1978;Gravel et al 2013), the strength of ecological interactions (Berlow et al 2009), trophic cascades (DeLong et al 2015), and food web structure (Brose et al 2006;Riede et al 2011;Gravel et al 2013;Gibert & DeLong 2014), all of which have ecosystem-level consequences (Anderson-Teixeira, Vitousek & Brown 2008;Trebilco et al 2013).…”
Section: Introductionmentioning
confidence: 99%